IMPLEMENTASI PENDEKATAN GROWTH, RESILIENCE, INNOVATION, TRUST DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SMP IT CAHAYA ISLAM SERPONG - Suprihatin Suprihatin; Mualif Mualif (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to analyze the role of Growth, Resilience, Innovation, and Trust (GRIT) in improving the quality of learning at SMP IT Cahaya Islam Serpong. The focus of this study includes: (1) the role of GRIT in the learning process, (2) the quality of learning in schools, and (3) the implementation of GRIT in improving the quality of education. This study uses a qualitative case study approach with data collection techniques through observation, in-depth interviews, and documentation. The data analysis technique uses a qualitative descriptive analysis interactive model of Miles, Huberman, and Saldaña (2014) which consists of data reduction, data presentation, as well as drawing conclusions and verification. The results of the study indicate that GRIT has an important role in forming an active, collaborative, and meaningful learning ecosystem. The Growth aspect encourages students to have a growth mindset, Resilience forms resilience in facing learning difficulties, Innovation increases creativity in the learning process, while Trust creates a positive and transparent relationship between teachers, students, and parents. The quality of learning at SMP IT Cahaya Islam Serpong is classified as good, characterized by increased student activity, effective learning interactions, and a student-centered learning process. Thus, the GRIT approach can be used as a framework for character building and learning management to holistically improve the quality of education in Islamic educational institutions.